Genomic sequencing and characterization of four human rhinovirus-c strains from Malaysian patients - Khaw, Yam Sim (2015)
Human rhinovirus (HRV) is one of the respiratory viruses responsible for acute respiratory tract infections (ARTI). HRVs infect both upper and lower respiratory tracts, especially in children. HRVs were initially classified into two clusters, HRV-A and HRV-B. A novel HRV strain, HRV-C was discovered in year 2006. There is a limited number of HRV-C complete genome in the GenBank. Hence, the objective of the present study is to sequence and characterize the Malaysian HRV-C complete genome. Four RNA samples were collected from children with respiratory signs and symptoms hospitalized in Universiti Malaya Medical Center (UMMC). These samples were previously confirmed as HRV-C by sequencing of VP4/VP2 region. Two steps reverse transcription polymerase chain reaction (RT-PCR) was performed. The complete genome was amplified using several sets of modified and redesigned primers. To understand the phylogenetic relationship of Malaysian HRV-Cs, MEGA6 software was used to construct phylogenetic trees. Characteristics of Malaysian HRV-C were determined and recombination was investigated using Recombination Detection Program (RDP) software. Approximately 7.1 kbp of four Malaysian HRV-Cs complete genome sequences were obtained. All the genes in Malaysian HRV-C coding region exhibited similar genomic features as other HRV-Cs. Malaysian HRV-C showed similar receptor utilization, immunogenic sites and antiviral sites with other HRV-Cs. Based on VP4/VP2 sequences, Malaysian HRV-Cs were classified as HRV-C6, C22, C23 and C42. Pairwise distance threshold further confirmed the classification based on VP4/VP2 sequences. Three Malaysian HRV-Cs (C22, C23 and C42) represent the first complete genome were successfully sequenced. No recombination was identified. Negative selective pressure was the dominant selective pressure exerted on Malaysian HRV-C and other HRV-Cs coding sequences. In conclusion, the present study provided four HRV-C complete genome sequences which will lead to a better understanding of functional sequences, predicted receptor usage, secondary structure and selective pressure in HRV-C.